Homogenized Water Vapor Absorption Band Radiances From International Geostationary Satellites. Issue 17 (4th September 2019) - Li, Zhenglong; Li, Jun; Gunshor, Mathew; Moeller, Szu‐Chia; Schmit, Timothy J.; Yu, Fangfang; McCarty, Will
Abstract: In the past 20+ years, GEO Imagers with infrared 6.5‐μm bands have been observing the Earth's atmosphere, providing useful information of upper tropospheric moisture. Due to the instrumental differences and local viewing angles in GEO satellites, these observations are not consistent for generating climate data records (CDRs). In this study, a methodology has been developed to homogenize the 6.5‐μm radiances from the international GEO satellites, to generate a consistent CDR. Validations with Infrared Atmospheric Sounding Interferometer radiances from Metops for 2015–2017 for seven GEO Imager sensors show that the GEO radiances are homogenized well with small standard deviation and biases of the differences (smaller for newer sensors), temporally stable radiometric accuracy, and weak angle dependency (even weaker for sensors with two water vapor bands). The homogenized 20+ years of consistent 6.5‐μm radiance CDR can be used to evaluate reanalysis and climate models, especially the diurnal variation of the model simulation. Key Points: Methodologies have been developed for consistent water vapor absorption infrared band radiances from multi‐instrument/multiplatform geostationary (GEO) satellites Consistent water vapor absorption infrared band radiances from GEO satellites as a climate data record (CDR) have been developed and validated; they are available for climate studies and model validation The methodologies and technical approaches can be applied to reprocess historical satellite data for consistent CDR and current GEO data in near real time for weather applications